Assessment of particle and heat loads to the upper open divertor in ASDEX Upgrade in favourable and unfavourable toroidal magnetic field directions. (May 2019) - Paradela Pérez, I.; Groth, M.; Wischmeier, M.; Scarabosio, A.; Brida, D.; David, P.; Silvagni, D.; Coster, D.; Lunt, T.; Faitsch, M.; ,; ,
Highlights: Large database of L-mode upper single null plasmas in ASDEX Upgrade. Divertor plasma conditions depend on the toroidal magnetic field direction. Stronger tungsten radiation in BT  < 0 direction causes variation of Psep . Power detachment observed at both targets for both toroidal field directions. Particle detachment only observed at the outer target for BT  < 0 with I p = 0 : 8 MA . Abstract: Pairs of ASDEX Upgrade L-mode discharges with the toroidal magnetic field, BT, in the forward and reverse directions have been used to study the impact of neoclassical drifts on the divertor plasma conditions and detachment. The evolution of the peak heat flux and the total power loads onto both the outer and the inner targets depends significantly on the toroidal field direction: increasing the core plasma density affects mainly the heat loads in the BT  < 0 (unfavourable) direction, whereas increasing the plasma current has a larger impact on the heat loads for BT  > 0 (favourable). Ion saturation current measurements show similar trends to those of the IR heat flux data. These discrepancies are not only caused by drifts but also by different levels of radiated power in the core, thus the power across the separatrix, P sep . Tomographic reconstructions show that P sep is not constant within the entire dataset. Finally, at I p = 0.8 MA, a significant reduction of the peak heat flux is observed at both targets for both field directions. On the other hand, at I p = 0.6 MA, a reduction of the peak heat flux is only observed for BT  < 0 at the outer target. Additionally, the onset of particle detachment is only observed at the outer target for BT  < 0 with I p = 0.8 MA .